2013
DOI: 10.1186/1749-8090-8-186
|View full text |Cite
|
Sign up to set email alerts
|

The effect of venovenous extra-corporeal membrane oxygenation (ECMO) therapy on immune inflammatory response of cerebral tissues in porcine model

Abstract: BackgroundExtra-Corporeal Membrane Oxygenation (ECMO) therapy is associated with high risk of neurologic injury. But the mechanism of neurologic injury during and/or after ECMO therapy is still unclear. Recent animal experiments confirmed that ECMO treatment increases the immune inflammatory response. The aim of this study is to investigate the effect of VV- ECMO on immune inflammatory response of cerebral tissues and neurological impairment.Methods18 porcine were randomly divided into control, sham and ECMO g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 36 publications
2
35
0
Order By: Relevance
“…Levels of pro-inflammatory cytokines rise rapidly [1319], which, in association with activation of the complement and contact systems [2025], results in leukocyte activation [2628]. This innate immune response, if severe, persistent or unchecked by a compensatory anti-inflammatory response (CARS) [29], may lead to endothelial injury, disrupted microcirculation, and end-organ dysfunction [3035]. Despite major improvements in pump and circuit design, oxygenators and the advent of heparin-bonded surfaces, the SIRS response to ECMO remains a clinical concern.…”
Section: The Inflammatory Response To Ecmomentioning
confidence: 99%
“…Levels of pro-inflammatory cytokines rise rapidly [1319], which, in association with activation of the complement and contact systems [2025], results in leukocyte activation [2628]. This innate immune response, if severe, persistent or unchecked by a compensatory anti-inflammatory response (CARS) [29], may lead to endothelial injury, disrupted microcirculation, and end-organ dysfunction [3035]. Despite major improvements in pump and circuit design, oxygenators and the advent of heparin-bonded surfaces, the SIRS response to ECMO remains a clinical concern.…”
Section: The Inflammatory Response To Ecmomentioning
confidence: 99%
“…ECMO is a relatively new technology; therefore, further research is needed to ascertain its clinical utility. Our previous studies revealed that ECMO therapy may injure the heart [ 12 , 13 ], kidney [ 14 ], and brain [ 15 ]. Other recent case reports show that ECMO therapy can increase intra-abdominal pressure [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, systemic inflammation (e.g., elevated c-reactive protein, elevated pro-inflammatory cytokines) has been documented in neonates with ECMO [30, 31], as well as in neonates with clinical sepsis [32] and studies have demonstrated that creatine is often elevated alongside choline in the setting of cerebral inflammation [25, 27]. Taken together, the elevations in creatine and choline suggest that the systemic inflammatory response could extend to the central nervous system, as demonstrated in animal models [33]. …”
Section: Discussionmentioning
confidence: 99%